SOCIAL SETTING AND MESSAGES IN MAHER ZAIN’S SELECTED SONGS - Imam Sudarmaji (JIPIS, 2019)
This article presents in analyzing the social setting in Maher Zain’s selected songs in an effort to discover the messages in the songs. In order to find out the social setting and messages hidden in the songs, the sociolinguistic theory is used to uncover the messages of the social setting found in Maher Zain’s selected songs.